ANALISIS EFEKTIVITAS METODE PEMBELAJARAN DARING DI SD PADA MASA PANDEMI COVID-19 - Anis Kurniawati; Nabbila Dinda Pramesti; Ratu Ayu Dewi Sartika (Jurnal Pendidikan, 2022)
At the beginning of 2020, the world was faced with a new type of health epidemic, namely COVID-19. This pandemic causes new habits and changes in people's lifestyles, including in learning. The government established a new regulation regarding online learning in Indonesia. However, this certainly creates some obstacles for students, parents, teachers, and even educational institutions. Purpose: Find out whether online learning is effective in terms of students, parents, teachers, and educational institutions. Purpose: The purpose of this paper is to find out whether online learning is effective in terms of students, parents, teachers, and educational institutions. Methods: The research was conducted using a literature review method using secondary data. Results: The results of the analysis show that the obstacles experienced by students in online learning include decreased learning motivation due to boredom, material that is not understood due to limited facilities. Barriers to parents include the economic conditions affected by the COVID-19 pandemic, which do not support learning, and less time to accompany students. Barriers to teachers include lack of knowledge and skills regarding technology and limited learning interactions. Meanwhile, obstacles from educational institutions include re-planning and supervision that is hampered in the implementation of online learning.